Hard Coral (Porites Lutea) Growth Simulation using Fuzzy Logic Method in Tunda Waters, Banten Province (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2026)
Corals grow annually at varying rates, influenced by environmental conditions. As key indicators of marine ecosystem health, studying coral growth is essential for predicting the impacts of environmental change. While previous research has explored coral growth extensively, most studies focus on existing conditions and the descriptive influence of environmental parameters. In fact, coral growth time-series data offer potential for deeper analysis, particularly in identifying dominant periodicities and enabling long-term projections. This study aims to develop an annual coral growth model using fuzzy logic approach. The Indian Ocean Dipole (IOD) is identified as a significant factor influencing the growth of Porites lutea in Tunda Island. Variations in sea surface temperature during IOD events notably affect coral growth, with positive IOD phases (IOD+) generally enhancing it. Analysis shows that the annual growth rings of Porites lutea in the northern station of Tunda Island, which borders open waters respond more slowly to SST fluctuations compared to the southern station, which is more sheltered. Fuzzy simulation results suggest that corals may be able to adapt to climate change. By the year 2085, coral growth is projected to recover from -0.75 cm to 0.1 cm by 2100. Based on SST projections from 1900 to 2100, SST anomalies are expected to continue increasing, reaching +0.45 °C.